Perbandingan Perilaku Struktur Kolom Berjenjang dan Tidak Berjenjang Gedung FMIPA Universitas Gadjah Mada Yogyakarta - Fernando Priatama; Sudirman Indra; Mohammad Erfan (Jurnal Spesialis Teknik Sipil (JSpTS), 2026)
Yogyakarta is located in a high seismic risk zone, making earthquake-resistant structural design essential especially for multi-story educational buildings like the FMIPA UGM facility. This study compares two structural configurations: stepped columns and non-stepped columns, using the Special Moment Resisting Frame System (SMRFS) in accordance with SNI 1726:2019, SNI 1727:2020, and SNI 2847:2019. Structural analysis was conducted using ETABS software to evaluate key parameters such as fundamental period, base shear force, and inter-story drift. The results reveal that the stepped column configuration yields a shorter vibration period, lower base shear, and reduced inter-story drift compared to the non-stepped column structure. The maximum drift occurs on the 10th floor, with a difference of 19.19% in the X direction and 16.2% in the Y direction. These findings suggest that stepped columns enhance structural efficiency and seismic performance in multi-story buildings. Moreover, the stepped configuration may reduce structural damage and improve occupant comfort during seismic events. This research contributes valuable insights to the development of earthquake-resistant design strategies in disaster-prone regions, offering practical recommendations for engineers and designers seeking to optimize structural resilience and safety.